2020
DOI: 10.1002/cne.24855
|View full text |Cite
|
Sign up to set email alerts
|

The role of PDLIM1, a PDZ‐LIM domain protein, at the ribbon synapses in the chicken retina

Abstract: PDLIM's protein family is involved in the rearrangement of the actin cytoskeleton. In the present study, we describe the localization of PDLIM1 in chicken photoreceptors.This study provides evidence that this protein is present at the cone pedicles, as well as in other synapses of the chicken retina. Here, we demonstrate the expression pattern of PDLIM1 through immunofluorescence staining, immunoblots, subcellular fractionation, and immunoprecipitation experiments. Also, we consider the possibility that PDLIM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…PDLIM3 and PDLIM7 are two members of the PDZ and LIM domain (PDLIM) family, participating in multifunctional protein-protein interaction, cytoskeleton, and signal transduction pathways [ 44 ]. PDLIM family proteins contain a PDZ domain in the N-terminal portion and the LIM domain in the C-terminal portion [ 45 ]. PDLIM1 and PDLIM7 were previously identified as negative biomarkers of beef tenderness [ 13 ], which was consistent with our results stating that PDLIM3 and PDLIM7 were positively correlated with WBSF and the negative relationship of this protein family with beef quality.…”
Section: Discussionmentioning
confidence: 99%
“…PDLIM3 and PDLIM7 are two members of the PDZ and LIM domain (PDLIM) family, participating in multifunctional protein-protein interaction, cytoskeleton, and signal transduction pathways [ 44 ]. PDLIM family proteins contain a PDZ domain in the N-terminal portion and the LIM domain in the C-terminal portion [ 45 ]. PDLIM1 and PDLIM7 were previously identified as negative biomarkers of beef tenderness [ 13 ], which was consistent with our results stating that PDLIM3 and PDLIM7 were positively correlated with WBSF and the negative relationship of this protein family with beef quality.…”
Section: Discussionmentioning
confidence: 99%
“…This includes receptors such as the insulin receptor (INSR) [ 30 ], the tyrosine kinase RET [ 31 ], neurotrophin receptor p75 [ 32 ] and the α7 subunit of the nicotinic acetylcholine receptor [ 33 ] as well as cytoplasmic proteins such as NF-κB [ 34 ] and protein kinase C [ 35 , 36 ]. Taken together with the observation that PDLIM1 localises to the synaptosomes of chicken retina [ 37 ], and our own observation that a small pool of PDLIM5 and 7 colocalise with the EEA1-positive endosomes as well as the selective nature of the PDLIM PDZ domain for the type III PDZ-binding motif (PDZbm) found in SNX17 it suggests this protein family plays key roles in membrane trafficking pathways [ 3 ]. While the exact nature of this role is unclear at present it is worth noting that in 2004 Schulz et al demonstrated that PDLIM4 could simultaneously interact with α-actinin, through its PDZ domain, and the cytoplasmic tail of the GluR-A subunit of the AMPA receptor, through the LIM domain [ 38 ].…”
Section: Introductionmentioning
confidence: 63%
“…However, till now, the studies on PDLIM1 in ocular diseases are mainly lacking. By observing chicken retinas, Hugo et al 18 found that PDLIM1 primarily localizes in the inner and outer plexus layer, the outer edge layer of muller cells, and photoreceptor cells. Their results showed that this protein also exists in the cone pedicle and other synapses of chicken retinas 18 .…”
Section: Discussionmentioning
confidence: 99%
“…By observing chicken retinas, Hugo et al 18 found that PDLIM1 primarily localizes in the inner and outer plexus layer, the outer edge layer of muller cells, and photoreceptor cells. Their results showed that this protein also exists in the cone pedicle and other synapses of chicken retinas 18 . Similarly, our immunofluorescence staining suggested that PDLIM1 was mainly located in the RPE in the mouse retina.…”
Section: Discussionmentioning
confidence: 99%